Gender Violence Against Indonesian Women in Ziggy Zezsyazeoviennazabrizkie’s Tiga dalam Kayu: A Feminist Literary Analysis - Wini Iga Munggarani; Rudi Adi Nugroho; Yulianeta, Yulianeta (South Asian Journal of Social Sciences and Humanities, 2025)
Purpose: This research aims to analyze the representation of violence against women in Indonesia as depicted in the novel Tiga Dalam Kayu by Ziggy Zezsyazeoviennazabrizkie. The study seeks to explore how social constructions often perpetuate violence against women in Indonesia from a feminist perspective. This research is grounded in the pervasive issue of violence against women in Indonesia, encompassing cases of domestic violence, sexual abuse, and even murder. Methodology: The study employs a descriptive qualitative method with a literature review approach to achieve its objectives. Mansour Fakih’s theory of gender-based violence is utilized to analyze the portrayal of violence against women in the novel. Main Findings: The findings reveal five distinct types of violence against women represented in Tiga Dalam Kayu: one instance of pornography, three instances of rape, five instances of physical violence, one instance of prostitution, and one instance of sexual harassment. These depictions of violence are shaped by historical and cultural contexts, alongside the deeply rooted patriarchal values that persist within Indonesian society. Applications: The study highlights how literature serves as a medium to capture and portray the harsh realities of human experiences, particularly the challenges faced by women. Novelty/Originality of This Study: The study underscores the novelist’s effort to represent the suffering endured by Indonesian women due to the prevalence of violence in their lives. By examining these portrayals, this research provides a deeper understanding of how literature reflects societal issues and challenges patriarchal norms.